Light induced hydrogen generation with silicon-based thin film tandem solar cells used as photocathode. (12th January 2015) - Kaiser, Bernhard; Calvet, Wolfram; Murugasen, Eswaran; Ziegler, Jürgen; Jaegermann, Wolfram; Pust, Sascha E.; Finger, Friedhelm; Hoch, Sascha; Blug, Matthias; Busse, Jens
Abstract Thin film tandem solar cells based on amorphous and microcrystalline silicon (a-Si:H/μc-Si:H) are employed as the cathode in a photoelectrochemical converter for solar water splitting. It is setup in such a way that the silver back contact of the cell is directly connected to the electrolyte and the light enters the cell through the glass substrate. This arrangement offers a number of distinct advantages compared to the conventional designs. The cathode is further optimized by the deposition of platinum nanoparticles to achieve higher conversion efficiencies. The front contact of the photovoltaic cell is connected to a standard platinum counter electrode in a three-electrode arrangement. Photon to current conversion efficiencies can reach up to 3% for our design, which has not been optimized to the requirements of the water splitting reaction, yet. The optimization of such tandem devices made from abundant silicon in combination with nanoparticle catalysts offers an affordable pathway for direct solar-to-fuel conversion devices in form of an artificial inorganic leaf.